Synthesis and Characterization of Nd:YAG Ceramics for Laser Applications - Olga Alondra Echartea-Reyes; Gloria Verónica Vázquez; José Adalberto Castillo-Robles; Juan López-Hernández; Carlos Adrián Calles-Arriaga; Wilian Jesús Pech-Rodríguez; Enrique Rocha-Rangel (Ceramics, 2023)
Materials known as Nd:YAG are crystalline materials of the cubic system made from the neodymium-doped yttrium aluminum garnet, which, among others, have excellent optical properties. Nd:YAG four-level laser devices are frequently used in both the health and industrial sectors. In this study, a simple and inexpensive alternative to manufacturing Nd:YAG materials through solid state reactions following powder processing routes was proposed. For this, an intense mixture of the precursor materials (Al2O3 and Y2O3) was carried out, followed by the addition of neodymium atoms to improve the optical properties of the resulting material. High-energy mechanical mixing of the precursor powders resulted in submicron particles with good size distributions of the powders. The advance of YAG formation was monitored by intermediate phase formation during heat treatment through interrupted tests at different temperatures and analysis by X-ray diffraction. From this analysis, it was found that reaction for the formation of the desired YAG is completed at 1500 °C. Fourier transform infrared spectroscopy analyses determined the presence of functional groups corresponding to the YAG. Finally, the study employing optical emission spectroscopy showed wavelengths in agreement with those of the electronic structure of the elements of the synthesized Nd:YAG.